2010
DOI: 10.1088/2043-6254/1/1/015008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Fe-doped TiO 2 photocatalyst by the sol–gel method

Abstract: Thin layers of pure TiO 2 and TiO 2 doped by different amounts of Fe 2 O 3 have been prepared by the sol–gel method with tetraisopropyl orthotitanate and Fe(NO 3)3. Physico-chemical properties of catalysts were characterized by BET Adsorption, x-ray Diffraction (XRD), FE-SEM, as well as Raman and UV-Vis spectroscopy. The photocatalytic activity of the obtained materials was investigated in the reaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 14 publications
6
49
0
Order By: Relevance
“…This may be related to the fact that TiO 2 and UiO66-NH 2 catalysts absorb the near-visible light of the high-intensity UV lamp, which facilitates the carbon deposit on the catalyst surfaces that should lead to reduce in activity. Meanwhile, the four catalysts of second group absorbed the visible light of lowlight LEDs, resulting in lower carbon deposit and catalysts work stability, as already found in article [34]. Perovskites LaFeO 3 and Cr-TiO 2 thin film were the best photo-catalysts under combined UV + LED illumination with a yield reached up to 1.70 g p-xylene /g cat .…”
Section: Photocatalytic Activity Of Catalyst Thin Filmsmentioning
confidence: 52%
“…This may be related to the fact that TiO 2 and UiO66-NH 2 catalysts absorb the near-visible light of the high-intensity UV lamp, which facilitates the carbon deposit on the catalyst surfaces that should lead to reduce in activity. Meanwhile, the four catalysts of second group absorbed the visible light of lowlight LEDs, resulting in lower carbon deposit and catalysts work stability, as already found in article [34]. Perovskites LaFeO 3 and Cr-TiO 2 thin film were the best photo-catalysts under combined UV + LED illumination with a yield reached up to 1.70 g p-xylene /g cat .…”
Section: Photocatalytic Activity Of Catalyst Thin Filmsmentioning
confidence: 52%
“…Infrared spectroscopy revealed that no modification of the cotton could be detected after photo-discoloration processes with TiO 2 -SiO 2 , taking a wine stain as model compound. The mixed TiO 2 and SiO 2 colloids lead during the dip-coating and subsequent thermal treatment on cotton to an organized structure of highly dispersed TiO 2 particles always surrounded by amorphous silica [4,6,7,8]. Therefore, this study demonstrates that the photocatalytic activity of TiO 2 -SiO 2 coated and TiO 2 coated on 100% cotton and PES/Co fabrics can be successful by the self-cleaning of red wine stains and coffee stains.…”
Section: Introductionmentioning
confidence: 61%
“…This evolution could be linked to the presence of acceptor states in the bandgap. Transition metals could also make significant changes on the electronic structure of a crystalline material and thus on the values of the gap energy [25] [26]. The decrease in the gap energy makes TiO 2 -Cr films wider range absorbers of UV-Visible light, constituting a major advantage in terms of photovoltaic applications.…”
Section: Resultsmentioning
confidence: 99%